2004
DOI: 10.1196/annals.1293.030
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mitochondrial DNA Mutations in Oral Cancer of Betel Quid Chewers

Abstract: Somatic mitochondrial DNA alteration is a general phenomenon that occurs in cancerous cells. Although numerous mtDNA mutations have been identified in various tumors, the pathogenic significance of these mutations remains unclear. In order to better understand the role of mtDNA mutations in the neoplastic process of oral cancer, the occurrence of mtDNA mutations in oral squamous cell carcinomas was screened by temporal temperature gradient gel electrophoresis (TTGE). The entire mitochondrial genome was amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Previously, Tan et al demonstrated that somatic mitochondrial DNA mutations occur in oral cancer with a history of betel quid chewing. Fourteen of 18 oral cavity SCC tumors (77.8%) had somatic mitochondrial DNA mutations with a total of 26 mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Tan et al demonstrated that somatic mitochondrial DNA mutations occur in oral cancer with a history of betel quid chewing. Fourteen of 18 oral cavity SCC tumors (77.8%) had somatic mitochondrial DNA mutations with a total of 26 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen of 18 oral cavity SCC tumors (77.8%) had somatic mitochondrial DNA mutations with a total of 26 mutations. Among them, 5 mutations were a cytidine‐to‐thymidine transition, and this type of mutation is similar to that induced by UV exposure . Furthermore, Hsieh et al analyzed the conserved regions of the p53 gene in 187 oral cavity SCC tumor specimens with various exposure histories of betel nut chewing, smoking, and alcohol drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 740 the 71d LHP was also found in samples of oral cancer of individuals 741 chewing betel quid (Tan et al, 2004). …”
mentioning
confidence: 95%
“…That mutation caused replacement of threonine with alanine. In the cells of intestinal crypts (Taylor et al 2003) and in the case of oral cancer – by proline (Tan et al 2004). …”
Section: Discussionmentioning
confidence: 99%